Quartz: Deposits, Mineralogy and Analytics - Götze, Jens; Möckel, Robert (Springer Geology,, 2012)
The book will include contributions of the state of the art of quartz raw materials (deposits and properties) and their analytics. The chapters are presented by leading scientists in the quartz field. The presentations cover the main interrelations between genesis of quartz - formation of specific properties - analytics - industrial applications of SiO2 raw materials.